PENINGKATAN HASIL BELAJAR SISWA KELAS IV DALAM MATA PELAJARAN PENDIDIKAN PANCASILA MATERI KEBUDAYAAN DAERAH DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) BERBANTUAN MEDIA BILIK KEBERAGAMAN DI SDN DIMONG 03 - Fifin Mustika Kusriati Rahayu; Ayu Arinda; Febi Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the learning outcomes of fourth grade students of SDN Dimong 03 in Pancasila Education subjects, especially regional culture material, through the application of the Think Pair Share (TPS) type cooperative learning model combined with concrete learning media “Bilik Keberagaman”. This research uses Classroom Action Research (PTK) method with two cycles, each of which consists of planning, implementation, observation, and reflection stages. The research subjects were 10 fourth grade students. Data collection techniques include observation, interviews, documentation, and learning outcomes tests. The results showed that the application of the TPS model assisted by the “Diversity Booth” media can improve student activity and learning outcomes. The average student score increased from 62 in the pre-cycle to 90 in cycle I, with the level of learning completeness reaching 100%. In addition, the application of the media also encourages students' active involvement, increases motivation, and fosters an attitude of tolerance and appreciation for cultural diversity. This research recommends the TPS model and concrete media as an effective alternative learning strategy in local culture-based character education.